Uma abordagem sobre passagens de fauna e ecologia de estrada como forma de mitigação e conservação da biodiversidade - Medeiros, Nataly Lorenza Baptistella (Universidade Federal de São Carlos, 2025)
The present study focuses on gathering research about wildlife crossings, also known as ecoducts or green bridges, their objectives, importance, and effectiveness in the conservation and mitigation of biodiversity loss among wild animals. The research adopted a qualitative and exploratory-descriptive approach, based on a bibliographic review of scientific articles, dissertations, and published technical reports. Wildlife crossings emerged in Europe and North America as a response to the fragmentation of natural habitats and the high mortality rates of animals due to roadkill. These ecoducts play a fundamental role in restoring connectivity between forest fragments, allowing species to move safely and maintaining ecological processes. In Brazil, although the topic is still developing, many authors have significantly contributed to studies on mitigation measures and the monitoring of wildlife crossings on Brazilian highways. This study discusses different types of crossings, such as vegetated overpasses, underground passages, and aerial bridges, designed to meet the specific needs of terrestrial and arboreal species. The results indicate that these structures effectively reduce habitat fragmentation, minimize roadkill, and preserve biodiversity. However, challenges such as high costs and the absence of public policies still limit their implementation. This research highlights the relevance of wildlife crossings as essential tools for promoting sustainable coexistence between road development and biodiversity conservation.
An approach to fauna passages and road ecology as a form of mitigation and conservation of biodiversity
Keywords: Ecologia de Estradas; Deslocamento da Fauna; Movimentação da Fauna; Conectividade de Habitats; Road Ecology; Habitats Conectivity; Fauna movements; Fauna displacement; CIENCIAS BIOLOGICAS::ECOLOGIA